Association of Leptin Promoter 2548G/A variant with Serum Leptin, Lipid Profile and Type 2 Diabetes Mellitus - H Abdullah, Gaylany (Diyala Journal of Medicine, 2020)
Background: A common 2548G/A promoter variant of the human leptin gene has been implicated in circulating leptin levels variations and pathogenesis of type 2 diabetes mellitus but available data are still conflicting. Objective: To explore potential associations between LEP 2548G/A of leptin with T2DM and the effect of this variation on serum leptin levels. Patients and Methods: Sixty two patients with T2DM and fifty non-diabetic controls were included in the study. Blood samples were collected from subjects for biochemical analysis and Genotyping was performed by polymerase chain reaction reaction–restriction fragment length polymorphism (PCR-RFLP). Results: The genotype frequencies for LEP 2548G/G, LEP 2548G/A LEP 2548A/A were 46%, 32% and 22% in control group, and 19.4%, 33.9% and 46.7% in diabetic group, respectively. The A allele and GA/AA genotype of LEP 2548G/A was found to be more frequent than the G allele and GG genotype in T2DM patients compares to the controls. Subjects with the GA + AA genotype of LEP 2548G/A were at increased risk for T2DM (P=0.0001, OR = 1.78; 95% CI: 1.19–2.38). The serum leptin concentration of GA + AA genotype carriers was significantly higher from that of the GG genotype in the diabetic group. Conclusion: A allele carrier who have higher serum concentrations of leptin may have an association with the risk of T2DM development in the Erbi population.